Diseño de socket de prótesis transfemoral, para disminución de lesiones causadas por presión en el muñón (2023)
This research exposes the design of a transfemoral prosthetic socket. The design begins with the review of preliminary studies, in which issues related to transfemoral amputation and possible solutions for patient-prosthesis incompatibility are addressed